Mechanical Ventilation Management During Extracorporeal Membrane Oxygenation for Acute Respiratory Distress Syndrome: A Retrospective International Multicenter Study*. Issue 3 (March 2015) - Schmidt, Matthieu; Stewart, Claire; Bailey, Michael; Nieszkowska, Ania; Kelly, Joshua; Murphy, Lorna; Pilcher, David; Cooper, D. James; Scheinkestel, Carlos; Pellegrino, Vincent; Forrest, Paul; Combes, Alain; et al.
Abstract : Objective: To describe mechanical ventilation settings in adult patients treated for an acute respiratory distress syndrome with extracorporeal membrane oxygenation and assess the potential impact of mechanical ventilation settings on ICU mortality. Design: Retrospective observational study. Setting: Three international high-volume extracorporeal membrane oxygenation centers. Patients: A total of 168 patients treated with extracorporeal membrane oxygenation for severe acute respiratory distress syndrome from January 2007 to January 2013. Interventions: We analyzed the association between mechanical ventilation settings (i.e. plateau pressure, tidal volume, and positive end-expiratory pressure) on ICU mortality using multivariable logistic regression model and Cox-proportional hazards model. Measurement and Main Results: We obtained detailed demographic, clinical, daily mechanical ventilation settings and ICU outcome data. One hundred sixty-eight patients (41 ± 14 years old; PaO2 /FIO2 67 ± 19 mm Hg) fulfilled our inclusion criteria. Median duration of extracorporeal membrane oxygenation and ICU stay were 10 days (6–18 d) and 28 days (16–42 d), respectively. Lower positive end-expiratory pressure levels and significantly lower plateau pressures during extracorporeal membrane oxygenation were used in the French center than in both Australian centers (23.9 ± 1.4 vs 27.6 ± 3.7 and 27.8 ± 3.6; p < 0.0001). Overall ICU mortality was 29%. Lower positive end-expiratory pressure levels (until day 7) and lower delivered tidal volume after 3 days on extracorporeal membrane oxygenation were associated with significantly higher mortality ( p < 0.05). In multivariate analysis, higher positive end-expiratory pressure levels during the first 3 days of extracorporeal membrane oxygenation support were associated with lower mortality (odds ratio, 0.75; 95% CI, 0.64–0.88; p = 0.0006). Other independent predictors of ICU mortality included time between ICU admission and extracorporeal membrane oxygenation initiation, plateau pressure greater than 30 cm H2 O before extracorporeal membrane oxygenation initiation, and lactate level on day 3 of extracorporeal membrane oxygenation support. Conclusions: Protective mechanical ventilation strategies were routinely used in high-volume extracorporeal membrane oxygenation centers. However, higher positive end-expiratory pressure levels during the first 3 days on extracorporeal membrane oxygenation support were independently associated with improved survival. Further prospective trials on the optimal mechanical ventilation strategy during extracorporeal membrane oxygenation support are warranted. Abstract : Supplemental Digital Content is available in the text.